Service quality, experiential value and repurchase intention for medical cosmetology clinic: moderating effect of Generation. (3rd July 2020) - Chang, Wen-Jung; Liao, Shu-Hsien; Chung, Yu-Chun; Chen, Hung-Pin
Abstract : Love of beauty is human's nature. The term anti-ageing has undoubtedly become the main stream of healthcare in the twenty-first century. However, the ultimate pursuit of medical cosmetology services/or procedures among Generations seems different. Different from consumer goods, medical cosmetic is a product of high involvement, risky invasive medical behaviour and professional skills. Therefore, lots of consumers would intuitively prefer a medical cosmetology clinic with its fine service quality, brand image or word-of-mouth. To any service firm, a long-term profitability is usually resulted from customer's repurchase intention and experiential value is likely to produce repurchase intention. Based on 350 valid respondents from a sample clinic in Chu-Li City, this paper aims to explore the relationships among service quality, experiential value and repurchase intention with an adoption of structural equation model. The empirical findings show that service quality and experiential value both positively impact repurchase intention. Besides, there is only partial moderating effect of Generation on the relationships among service quality, experiential value and repurchase intention.